Relationships among Caliothrips species (Thysanoptera: Panchaetothripinae) with one new species from Mexico - Mound, Laurence; Infante, Francisco (Zootaxa, 2017)
Caliothrips chiapas sp.n. is described from Mexico, breeding on the leaves but not in the flowers of Tithonia tubiformis [Asteraceae]. Patterns of tergal sculpture and wing colour exhibited by the 23 species now recognised in this genus are discussed and illustrated.